Does photoselective netting influence yield, chemical composition and antioxidant activities of essential oils in cultivated sage? - Milenković, Lidija; Ilić, Zoran S.; Stanojević, Ljiljana; Šunić, Ljubomir; Milenković, Aleksandra; Stanojević, Jelena; Cvetković, Dragan (Frontiers in Plant Science, 2025)
Yield, chemical profile and antioxidant activity of sage (Salvia officinalis L.) essential oils (SEOs) isolated from shaded (pearl, red and blue color nets) or non-shaded plants have been investigated. Analysis of the results can be seen a slightly higher amount of sage essential oil (SEO) from the shaded leaves samples, with minor exceptions. The highest yield of SEO was obtained from the samples cultivated under the blue photo-selective nets (1.97 mL/100 g p.m.). A total of 38 different components were identified in sage and divided into 7 groups. The main components of SEO were cis-thujone (32.9-35.2%), camphor (19.0-25.6%), trans-thujone (8.6-13.1%) and 1,8-cineole (9.4-11.0%).The strong antioxidant activity of all tested samples showed SEO from shaded sage leaves grown under the blue photoselective net for the all incubation times (20.00-37.28 mL/100 g p.m.).These researches confirmed that sage responded positively to blue light shading through increased production of secondary metabolic products such as EOs.